The Quantitative Meaning of Fractions for Mexican Sixth-Grade Students - José Luis Cortina Morfín; Ericka Renata Cardoso Moreno; Claudia Zúñiga Gaspar (Universidad Autónoma de Baja California, 2012)
This study consisted in the application of questionnaires to 297 sixth-grade students from 13 different elementary schools in Mexico. Pupils were asked to identify the quantity represented by common fractions (e.g., 1/2, 1/4, 1/3, 3/4). Findings suggest that many students are finishing elementary school in Mexico with a very limited understanding of fractions. Some seem not to have developed basic quantitative concepts that would allow them to readily and correctly recognize the quantitative meaning of the most common fractions, including "1/2". We explain the implications of such findings for students' future mathematical development.